Selection of stable and high-yielding lines of purple corn (Zea mays L.) var. popcorn using multi-trait stability index (MTSI) (Scientia Agropecuaria, 2022)
A novel approach to strengthen maize breeding strategies is the use of the multi-trait stability index (MTSI), this index allows the identification of more stable and high-yielding genotypes with greater reliability than previous methods. To select outstanding purple popcorn S1 lines based on the MTSI, 80 purple popcorn S1 lines were evaluated in three environments. 11 characteristics were studied: expansion volume (VE), pigmented pericarp (PP), grain yield (GY), expansion percentage (PE), male flowering (FM), ear length (LM), grain moisture (HG), plant height (AP), weight of 100 grains (PG), volume of 100 grains (VG) and expanded grain size (TG). The results indicated that the environmental differences contributed to a greater extent to the total variation, followed by the genotypic differences, both were significant for all the variables, in addition, the genotype x environment interaction was significant in 10 of 11 characteristics evaluated. According to the MTSI and with a selection pressure of 15%, 12 purple popcorn S1 lines were selected as the most stable and high yielding among the 80 genotypes evaluated. The selected S1 lines will be converted into double haploid lines and evaluated for their general and specific combinatorial abilities, likewise, the unknown antioxidant capacity will be determined.
Keywords: genotype x environment interaction; purple popcorn; principal component analysis; native Peruvian corn